Role of Vitamin D in Breast Cancer Prevention and Therapy: Recent Findings (Journal of Medicine, 2019)
Vitamin D, a fat-soluble vitamin, is produced in the skin exposed to the sunlight or provided by dietary intake. In addition to its role in the regulation of calcium and phosphorus metabolism, vitamin D has been correlated with several ailments such as depression, osteoporosis and cancer. Since vitamin D deficiency has been demonstrated to be linked to higher breast cancer risk, importance has been given to study its possible use in the prevention or even treatment of breast cancer. Herein, we review recent publications studying the vitamin D effects and breast cancer. Role of vitamin D as a preventive agent, its involvement in therapies and the effects of vitamin D supplementation are discussed. Accumulative findings support that vitamin D supplementation might reduce breast cancer risk, enhance effectiveness of chemotherapeutics and improve cancer survival.J MEDICINE JAN 2020; 21 (1) : 46-50